Interslice current change constrained B0 shim optimization for accurate high‐order dynamic shim updating with strongly reduced eddy currents. Issue 1 (18th March 2019) - Schwerter, Michael; Hetherington, Hoby; Moon, Chan Hong; Pan, Jullie; Felder, Jörg; Tellmann, Lutz; Shah, N. Jon
Abstract : Purpose: To overcome existing challenges in dynamic B0 shimming by implementing a shim optimization algorithm which limits shim current amplitudes and their temporal variation through the application of constraints and regularization terms. Theory and Methods: Spherical harmonic dynamic B0 shimming is complicated by eddy currents, ill‐posed optimizations, and the need for strong power supplies. Based on the fact that eddy current amplitudes are proportional to the magnitude of the shim current changes, and assuming a smoothness of the B0 inhomogeneity variation in the slice direction, a novel algorithm was implemented to reduce eddy current generation by limiting interslice shim current changes. Shim degeneracy issues and resulting high current amplitudes are additionally addressed by penalizing high solution norms. Applicability of the proposed algorithm was validated in simulations and in phantom and in vivo measurements. Results: High‐order dynamic shimming simulations and measurements have shown that absolute shim current amplitudes and their temporal variation can be substantially reduced with negligible loss in achievable B0 homogeneity. Whereas conventional dynamic shim updating optimizations improve the B0 homogeneity, on average, by a factor of 2.1 over second‐order static solutions, our proposed routine reached a factor of 2.0, while simultaneously providing a 14‐fold reduction of the average maximum shim current changes. Conclusions: The proposed algorithm substantially reduces the shim amplitudes and their temporal variation, while only marginally affecting the achievable B0  homogeneity. As a result, it has the potential to mitigate the remaining challenges in dynamic B0 shimming and help in making its application more readily available.